2020
DOI: 10.3390/vetsci7020045
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Investigation on Serum Amyloid A Concentration in Client-Owned Healthy and Diseased Cats in a Primary Care Animal Hospital

Abstract: Although measurement of serum amyloid A (SAA) concentration in client-owned cats has already been shown to be clinically useful, limited data are available on common diseases at primary care hospitals. In this study, we measured the SAA concentration in cats with various diseases and investigated their clinical significance using a primary care hospital as a population. We measured the SAA concentrations in healthy cats (n = 98) and those with various clinical signs (n = 444). The SAA concentrations in healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…Serum amyloid A (SAA) is an acute-phase plasma protein that produced by hepatocytes in response to the inflammatory cytokines such as TNF-α, IL-1β and IL-6 [ 14 ]. In humans, SAA is considered to be diagnostically superior to CRP in pathological conditions such as viral diseases and transplant rejection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) is an acute-phase plasma protein that produced by hepatocytes in response to the inflammatory cytokines such as TNF-α, IL-1β and IL-6 [ 14 ]. In humans, SAA is considered to be diagnostically superior to CRP in pathological conditions such as viral diseases and transplant rejection [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even so, this study was conducted in accordance with the ethical codes of the Japan Veterinary Medical Association. 30 Clinical score assessment and treatment for cAD…”
Section: Methods and Materials Animalsmentioning
confidence: 99%
“…However, in the present case, on day 43, SAA was 13.7 µg/ml, which is only slightly higher than the reference range (0-6.5 µg/ml). Previously, it was reported that cats with upper respiratory tract infections, pneumonia, pyometra, feline infectious peritonitis, trauma, and/or sepsis exhibited a median SAA of >100 µg/ml [20,24]. In cats with diabetic ketoacidosis (n = 8), the median SAA was reported as 4.1 μg/ml (interquartile range, 0.3-60.5 μg/ml) [24].…”
mentioning
confidence: 99%
“…Previously, it was reported that cats with upper respiratory tract infections, pneumonia, pyometra, feline infectious peritonitis, trauma, and/or sepsis exhibited a median SAA of >100 µg/ml [20,24]. In cats with diabetic ketoacidosis (n = 8), the median SAA was reported as 4.1 μg/ml (interquartile range, 0.3-60.5 μg/ml) [24]. As such, the low level of inflammation (13.7 µg/ml) in the current case would not have induced insulin resistance to the extent that 1.5 IU/kg insulin would be needed twice a day.…”
mentioning
confidence: 99%